Enhancing Dental Care through Interdisciplinary Collaboration: The Contributions of Dental Assistants, Social Workers, and Health Administrators - Ebtisam Abdullah Alhazeem; Thara Dhaifallah Al Habshn; Waleed Mohammed Binsaeed; Asma Ali Alenazi; Maram Faihan Albaqami; Amal Jalil Alshammari; Shymaa Abdo Abodui; Rami Ahmed Mohammed Alharbi; Mohammed Abdulrahman Al-Hadlaq; Sarah Saleh Mohammed Asiri; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
The team integration by dental assistants, social workers, and health administrators becomes quite an important strategy in pursuit of improving accessibility and raising the quality of service provision within oral health. This paper reviews the contribution of such professionals in enhancing patient care through interdisciplinary collaboration. The dental assistants ensure that clinical operations run smoothly, the social worker addresses the social determinants of health and navigates barriers to care for the patients, and the health administrator works out the most efficient ways administratively to operate a dental practice. In sum, these professionals contribute to improved patient activation, facilitate smoothing in care delivery, and better health outcomes. However, despite all these improvements, several challenges persist, including communications barriers and resource constraints that demand directed intervention. This review creates an avenue for dental professionals to work in interprofessional teams for the delivery of comprehensive person-centered dental care with a view toward better improvement of oral health equity.